Computer-aided stroke-by-stroke visualization of actual and target power allows for continuously increasing ramp tests on wind-braked rowing ergometers - Treff, G.; Winkert, K.; Machus, K.; Steinacker, J. M. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Ramp tests are continuously increasing exercise tests used for the determination of maximal oxygen uptake (V.O2max), which is identifiable by a plateau in oxygen uptake despite increasing mechanical power output (LOAD). On wind-braked rowing ergometers (RowErg), it is hardly feasible to ensure a continuous increase in LOAD until test termination, as neither resistance nor stroke frequency is externally adjustable but depends on the rower. To enable ramp tests on RowErg, the authors produced visual stroke-by-stroke feedback showing target and actual LOAD to the rower. The software supports automatic test termination (TERMauto) if LOAD ceases to increase. The authors aimed to evaluate linearity of the LOAD increment and calculate the difference between TERMauto and test duration at subjective exhaustion. Materials: Twenty-eight highly trained male rowers performed a ramp test until subjective exhaustion on RowErg, targeting an increment of 35 W·min-1. LOAD was measured as work per time via external force and position sensors and visualized on a computer screen. TERMauto was deactivated, but all data were logged. Test duration at subjective exhaustion was subsequently compared with virtual test duration at TERMauto calculated from the log files. Results: Regression between time and LOAD was y=167+34.6 W (r=.99). Individual correlations ranged from .97 to 1.0. TERMauto caused 12- to 35-s-shorter test durations than subjective exhaustion in 4 rowers, leading to an underestimation in VO2max not higher than 1.2% or 3.7%. Conclusion: This setup allows one to perform ramp tests on RowErg with continuously increasing LOAD until TERMauto. In particular cases VO2max might be slightly underestimated at TERMauto